(untitled) (European Journal of Social Sciences, 2022)
Aims. Even though child psychology researches related to a pandemic are extensive, the knowledge of practitioners about interventions and practices is still very limited. The complete novelty of such an epidemic situation in Europe, the diversity of terminology and methods are factors that make results hard to interpret. Therefore, the current study aims to give an overview of the psychological literature of the family aspects of the Covid-19 pandemic. Methods. A search was executed in four databases (Science Direct, Medline, Scopus, Google Scholar) using the following keywords: pandemic, Covid 19, family, children, adolescents, anxiety, depression. Our review focuses only on English language literature. Results. The majority of the articles focus on non-pathological phenomena and draws attention to the behavior of healthy populations (increase in internet use, the decline of concentration). Methods were dominated by online surveys. These surveys were mainly constructed ad-hoc and they preferred to address parents. Direct child investigations are underrepresented, but several suggestions were formulated for their optimal functioning. Conclusion:. Researches focusing on psychopathology emphasize the growth in the prevalence of disorders. However, other researches are needed to explore the psychodynamics of the pandemic on the family level. Our study aimed to contribute to the field by summarizing the main findings, suggestions, and interventions hoping that it might be a useful tool for practitioners and reduce the territory of the unknown.